Study on the relationship between SLCO1B1 and ApoE gene polymorphisms and the risk of coronary heart disease in the Mongolian population. (17th November 2021) - Niu, Rui-Bing; Dong, Xiao-Xian; Guo, Li-Ping; Pan, Li; Hai, Yue-Qin; Chen, Xiao-Xiao; Duan, Bao-Sheng
ABSTRACT: Objective This study aimed to analyze the influence of SLCO1B1 and APOE gene polymorphisms on coronary heart disease in Mongolian population who living in Ordos area. Methods From January 2019 to June 2020, 200 Mongolian patients with coronary heart disease admitted to our hospital and other banner hospitals were selected as the case group. At the same time, 150 randomly selected healthy Mongolian people from medical examination centers comprised the control group. The polymorphisms of SLCO1B1 (388A>G, 521 T > C) and ApoE (388 T > C, 526 C > t) were detected by real-time polymerase chain reaction. Combined with environmental data, the effect of gene polymorphism on coronary heart disease was explored. Results Both SLCO1B1 and ApoE polymorphisms satisfied Hardy-Weinberg equilibrium. The SLCO1B1 genotype *1a/*1b showed the highest frequency in the case group, accounting for 35.0%, while The SLCO1B1 genotype *1b/*1b showed the highest frequency in the control group, accounting for 32.0%. Allele *1b was the most commonly seen allele in both the case group and control group (57.8% and 53.7%, respectively). Meanwhile, The difference in the distribution of SLCO1B1 *1a/*15 genotype between the two groups was statistically significant ( P < .05). Conclusion The results showed that the SLCO1B *1a/*15 genotype, ApoE ε3 /ε3 genotype, and ε3 allele reduced the risk of coronary disease in the Mongolian population, making them protective genes against this disease, while the ApoE ε4 allele increased the risk of coronary disease, making it a coronary disease risk factor.